Proximity Ligation Assay Detection of Protein-DNA Interactions-Is There a Link between Heme Oxygenase-1 and G-quadruplexes? - Wojciech Krzeptowski; Patryk Chudy; Grzegorz Sokołowski; Monika Żukowska; Anna Kusienicka; Agnieszka Seretny; Agata Kalita; Alicja Czmoczek; Jakub Gubała; Sonia Baran; Damian Klóska; Mateusz Jeż; et al. (MDPI AG, 2021)
G-quadruplexes (G4) are stacked nucleic acid structures that are stabilized by heme. In cells, they affect DNA replication and gene transcription. They are unwound by several helicases but the composition of the repair complex and its heme sensitivity are unclear. We found that the accumulation of G-quadruplexes is affected by heme oxygenase-1 (Hmox1) expression, but in a cell-type-specific manner: hematopoietic stem cells (HSCs) from Hmox1−/− mice have upregulated expressions of G4-unwinding helicases (e.g., Brip1, Pif1) and show weaker staining for G-quadruplexes, whereas Hmox1-deficient murine induced pluripotent stem cells (iPSCs), despite the upregulation of helicases, have more G-quadruplexes, especially after exposure to exogenous heme. Using iPSCs expressing only nuclear or only cytoplasmic forms of Hmox1, we found that nuclear localization promotes G4 removal. We demonstrated that the proximity ligation assay (PLA) can detect cellular co-localization of G-quadruplexes with helicases, as well as with HMOX1, suggesting the potential role of HMOX1 in G4 modifications. However, this colocalization does not mean a direct interaction was detectable using the immunoprecipitation assay. Therefore, we concluded that HMOX1 influences G4 accumulation, but rather as one of the proteins regulating the heme availability, not as a rate-limiting factor. It is noteworthy that cellular G4-protein colocalizations can be quantitatively analyzed using PLA, even in rare cells.